O NATURZE PRAWNEJ DOMENY INTERNETOWEJ - Brancus-Cieślak, Lavinia (Zeszyty Prawnicze, 2017)
LEGAL NATURE OF AN INTERNET DOMAIN NAME Summary The paper reviews a legal nature of an Internet domain name, in both technical and commercial aspects. Technically, a domain name can be re- garded as an Internet communication address related to the Website and can be treated like a traditional telephone number or a post address. The equivalence between a domain name’s commercial function as an intangible asset and a trademark is analysed. The domain name hardly matches full legal characteristics of a trademark. The basic function of a trademark, i. e. identification of the source of goods or services is an example. Another example is a discrepancy between the distinctive character of a trademark and descriptive or generic character of most of domain names. Alternatively, the similarity of a domain name to a trade name is analysed as apparently more appropriate as its notion is drawn up by the Polish doctrine and jurisprudence rather than defined by the law. Furthermore, similarity of a domain name to a work protected by Copyright is also indicated. It appears inappropriate when domain name’s lack of original character is considered. An issue whether every domain name can be considered an object of moral rights provided by article 24 of the Civil Code is also indicated. It is concluded that no unambiguous definition can be applied to a domain name as well as no similarities to already existing rights protected by Polish law can be drawn up. Its definition depends on the domain name’s commercialfunction with which it is used in a particular case.